Adoption of e-banking in Islamic banking institutions among Muslim customers in Kedah - Nur Farrah Ain, Zainuddin (2014)
Electronic banking or known as e-banking is not a new phenomenon to the people nowadays. Developments in information technology and telecommunications have set in motion an electronic revolution in the Malaysian banking sector. Starting with the Automated Teller Machines (ATM) in 1970s till the introduction of Internet banking in the year 2000s, electronic banking has become an important product and services provided by the banking institutions including Islamic banks in Malaysia. This study aims to explore the determinants which influence the adoption of ebanking services provided by Islamic banks in Malaysia among Muslim customers. The determinants obtained by the researcher from the previous studies are perceived usefulness, perceived ease of use, security, trust and cost and charges. Findings show that all the determinants have a positive relationship with the e-banking adoption while in term of effects, there are three variables influence the adoption. Out of the three determinants, perceived usefulness is found to give the most influence towards e-banking adoption. Recommendation for the future research is religiosity to be added as one of the determinants to predict adoption of e-banking in Islamic banks